Implementation of Guidance and Counseling Services by Primary School Teachers - Sholeh, Mohammad Nur (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2023)
The objective of this study is to examine the implementation of guidance and counselling services by class instructors in elementary schools. The present study employed a descriptive qualitative methodology. The data collection methods employed in this study encompassed observation, interviews, and documentation. The individuals providing information for this study consisted of class teachers, school principals, and deputy principals responsible for curriculum affairs. The data underwent analysis through processes of data reduction, data display, and conclusion or verification. The method of source triangulation was selected in order to enhance the trustworthiness of the data. The findings indicate that the implementation of guidance and counselling services by instructors was executed well, resulting in the establishment of a structured and supportive learning environment. The integration of guidance and counselling services into primary school settings involved the incorporation of essential and fundamental competencies outlined in the semester's lesson plan. Teachers can enhance their understanding of their students by prioritising guiding actions aimed at enhancing the efficacy and efficiency of the teaching and learning process.